Rural people's perception of poverty in China - Björn Gustafsson; Ximing Yue (Institute for the Study of Labor (IZA), 2006)
Subjective Poverty Line methodology is applied to rural China 2002 using a sample from 22 provinces. Respondents were asked two questions: one on amount of food necessary and another on amount of cash necessary for their households. The respondent's perception of how much cash is needed varies profoundly and positively by income in the county where the respondent lives. The findings provide an argument for increasing the official poverty line for China as average household income increases. Poverty in rural China is disproportionally concentrated to the western regions and to poor counties. Most of rural China's poverty can be attributed to households living outside classified poor areas. People living in a household with many members, those with a household head with a short education, and children face higher poverty risks than other persons.
urn:nbn:de:101:1-2008051331
Keywords: 330